Judicial practice and its role in the development of the national legislation of the Republic of Kazakhstan - Abdrasulov Е.Б.; Ryszhanova Г.С.; Saktaganova А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Theoretical and practical significance of the topic of judicial practice is predetermined by the increasing influence of its role in the development and improvement of national legislation. In the system of separation of powers, the judiciary traditionally refrains from creating new legal regulations, ensuring only the application of legal norms in the process of justice. At the same time, the system of separation of powers assumes not only mechanisms of checks and balances, but also methods of interaction of various branches of government. In the process of such work, it is possible and necessary for the judicial system to participate in the development and improvement of legislation. Specification and detailing of the norms of laws is carried out today in the process of adopting regulatory decisions of the Supreme Court of the Republic of Kazakhstan, established in the Constitution of the Republic of Kazakhstan as a valid law. However, not only in the process of direct law-making it is possible for the judiciary to develop a system of norms of national law. Judicial practice as a plurality of judicial acts formed in the course of the activities of judicial bodies, their generalization by judicial collegiums of the Supreme Court of the Republic of Kazakhstan act as an auxiliary source of law, filling in gaps in the current legislation, offering recommendations for improving the mechanism of legal regulation and thereby ensuring its development and improvement. In this aspect, an important direction in the study of judicial practice today is the scientific understanding of the question of how far the limits of judicial law-making extend, what is its relationship with the interpretation of law, the judicial consciousness of the judge, the application of law and the law by analogy, what are the legal principles of judicial practice. The article examines these issues with the analysis of court decisions and their generalizations.